Improvements in setting behavior and strengths of cement paste/mortar with EVA redispersible powder using C-S-Hs-PCE. (30th November 2020) - Li, Haoxin; Gu, Linan; Dong, Biqing; Chen, Qing; Xu, Chao; Yang, Xiaojie; Wang, Weishan
Highlights: C-S-Hs-PCE cuts down the setting behavior of paste with EVA-DP. It increases the strengths at 3d of mortars with EVA-DP. It promotes hydration of paste with EVA-DP at different levels. It enhances the apparent density of mortar with EVA-DP. Abstract: This work aimed to improve the setting behavior and strengths of cement paste/mortar with ethylene and vinyl acetate copolymer redispersible powder (EVA-DP) using C-S-H seeds and polycarboxylate superplasticizer (C-S-Hs-PCE) and meanwhile explore the reasons for these two improvements by means of the heat flow, water requirement, air content, apparent density and pore size distribution. The experimental results show that C-S-Hs-PCE used in this work notably cuts down the setting behavior and increases the strengths at 3d of mortars with EVA-DP; however, less than 2% C-S-Hs-PCE hardly increases their strengths at 28d. C-S-Hs-PCE promotes the hydration of paste with EVA-DP in several manners; it enhances heat flow in the first deceleration period, the initial several hours in the acceleration period and at the main exothermic peaks/merged peak, or advances the onset of the acceleration period, or shifts the maximum of the hydration rate to earlier time. This promotion in the hydration at different levels is the reason for the shortened setting behavior of paste with EVA-DP in the presence of C-S-Hs-PCE. Except for the promoted hydration, the increased apparent density resulted from lowered water requirement, as well as the less pores, especially the middle and large capillary pores, are the other main contributors to the increment in the strengths of mortar with EVA-DP and C-S-Hs-PCE, especially the strengths at 28d of the mortars with 6% and 10% EVA-DP and 2% C-S-Hs-PCE.